2008
DOI: 10.1088/0022-3727/41/18/185406
|View full text |Cite
|
Sign up to set email alerts
|

Melting tungsten nanoparticles: a molecular dynamics study

Abstract: We report a molecular dynamics simulation of melting of tungsten (W) nanoparticles. The modified embedded atom method (MEAM) interatomic potentials are used to describe the interaction between tungsten atoms. The melting temperature of unsupported tungsten nanoparticles of different sizes are found to decrease as the size of the particles decreases. The melting temperature obtained in the present study is approximately a decreasing function of inverse radius, in a good agreement with the predictions of thermod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 55 publications
4
19
0
Order By: Relevance
“…Thus, we can conclude that a temperature corresponding to the melting point of the W particle was reached at the interface and the CNT did withstand such heating. To estimate this temperature, we used a phenomenological formula [19] relating the melting point T m of a W particle with its diameter R as T m (R) = T * (1 − R 1 /R), where T * is the melting point of bulk tungsten and R l = 2.2 nm is a fitting parameter [19]. Using the values of R = 30 nm and T * ∼ 3700 K [12], we obtain T m ∼ 3400 K. This temperature of CNT up to which it is stable is much higher than those reported previously [7,9] and is close to the theoretical limit [10].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we can conclude that a temperature corresponding to the melting point of the W particle was reached at the interface and the CNT did withstand such heating. To estimate this temperature, we used a phenomenological formula [19] relating the melting point T m of a W particle with its diameter R as T m (R) = T * (1 − R 1 /R), where T * is the melting point of bulk tungsten and R l = 2.2 nm is a fitting parameter [19]. Using the values of R = 30 nm and T * ∼ 3700 K [12], we obtain T m ∼ 3400 K. This temperature of CNT up to which it is stable is much higher than those reported previously [7,9] and is close to the theoretical limit [10].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows that the results of DFT calculations and experimental values are reproduced satisfactorily by the MEAM parameters for W. In particular, the elastic constants are well matched with the experimental values, although the present MEAM parameters show a tendency to underestimate the bulk modulus and surface energies. This shortcoming causes W nanoparticles to melt at lower temperatures due to premature pre-melting of surface layers [21].…”
Section: Atomic Potential For Molecular Dynamic Simulationmentioning
confidence: 99%
“…We have discussed the melting response of bulk and various sizes of nanoparticles from atomistic molecular dynamic simulations more extensively in Ref. [21]. In practice, the isothermal condition of constant NVT simulation would be maintained by immersing nanoparticles in a solvent with a sufficient density such as helium gas to facilitate the heat transfer between the nanoparticles and a heat bath.…”
Section: Temperature Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the huge progress enabled by these extensive studies, a few atomistic simulations on W clusters have been reported, but the structural details of the W clusters were not presented [20,21]. Though the electronic structure of W nanoscale clusters can be fully captured by DFT calculations, it is computationally demanding for DFT to explore the configurational space and find the global minimum of clusters with hundreds or thousands of atoms.…”
Section: Introductionmentioning
confidence: 99%